Rola ruchu w funkcjonowaniu grupy społecznej seniorów – popularyzacja strategii aktywności fizycznej = The role of movement in seniors' social group functioning - popularization of physical activity strategy - Dąbska, Olga; Humeniuk, Ewa; Pawlikowska-Łagód, Katarzyna; Firlej, Ewelina; Janiszewska, Mariola (Journal of Education, Health and Sport, 2016)
Dąbska Olga, Humeniuk Ewa, Pawlikowska-Łagód Katarzyna, Firlej Ewelina, Janiszewska Mariola. Rola ruchu w funkcjonowaniu grupy społecznej seniorów – popularyzacja strategii aktywności fizycznej = The role of movement in seniors' social group functioning - popularization of physical activity strategy. Journal of Education, Health and Sport. 2016;6(5):276-290. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51573 http://ojs.ukw.edu.pl/index.php/johs/article/view/3525 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.04.2016. Revised 10.05.2016. Accepted: 18.05.2016. Rola ruchu w funkcjonowaniu grupy społecznej seniorów – popularyzacja strategii aktywności fizycznej The role of movement in seniors' social group functioning - popularization of physical activity strategy Olga Dąbska, Ewa Humeniuk, Katarzyna Pawlikowska-Łagód, Ewelina Firlej, Mariola Janiszewska Olga Dąbska Affiliation mgr Zdrowia Publicznego, doktorantka Wydziału Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie Ewa Humeniuk Affiliation Zakład Patologii i Rehabilitacji Mowy, Uniwersytet Medyczny w Lublinie Katarzyna Pawlikowska-Łagód Affiliation Zakład Etyki i Filozofii Człowieka, Uniwersytet Medyczny w Lublinie Ewelina Firlej Affiliation Katedra Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie Mariola Janiszewska Affiliation Katedra Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie Słowa kluczowe: aktywność ruchowa, polityka społeczna, stan zdrowia, osoby starsze Streszczenie Zagadnieniem idealnie wpisującym się w zbiór działań polityki społecznej wobec procesu starzenia jest popularyzowanie aktywnego trybu życia, w tym coraz częściej podkreśla się rolę sportu. Aktywność fizyczna uznawana jest za jeden z najważniejszych elementów zdrowego stylu życia oraz czynnik determinujący stan zdrowia fizycznego i psychicznego jednostki. W związku z bardzo niskim poziomem uprawiania sportu wśród polskich seniorów, a także licznych czynników uniemożliwiających aktywne spędzanie czasu, coraz częściej podkreśla się znaczenie publicznych kampanii informacyjno-edukacyjnych, których celem jest uświadamianie korzyści zdrowotnych płynących z prowadzenia aktywnego stylu życia. Celem pracy jest przedstawienie pozytywów płynących z podejmowanej przez osoby w wieku geriatrycznym aktywności fizycznej. Uściślenie barier i motywów uprawiania ruchu przez seniorów. Przybliżenie akcji prozdrowotnych, ukierunkowanych na popularyzację sportu w grupie 65+. Zastosowano metodę analizy piśmiennictwa. Na podstawie dokonanego przeglądu piśmiennictwa nasuwają się wnioski: Regularnie podejmowana aktywność fizyczna to główny determinant zachowania dobrej kondycji zdrowotnej oraz niezależności wśród starszej grupy społecznej. Konieczne jest rozszerzenie zakresu działań w obszarze aktywizacji seniorów, szczególnie zaś dotyczących aktywności ruchowej, poprzez sukcesywne wdrażanie programów profilaktycznych z zakresu pomyślnego procesu starzenia się. Podejmowana w sposób regularny i dostosowana do stanu seniora aktywność fizyczna odracza wizję niepełnosprawności, zależności od osób trzecich czy objęcia opieką instytucjonalną. Podnosi prawdopodobieństwo niezależnej, komfortowej jesieni życia. Key words: motor activity, public policy, health status, frail elderly Summary The popularization of an active lifestyle is an issue that fits perfectly into social politics' set of activities regarding ageing process. The importance of sports is emphasised more and more often. Physical activity is deemed one of the most important aspects of a healthy lifestyle and a determining factor of physical and mental well-being of an individual. The level of physical activity among Polish seniors is very low and elderly face a lot of restrictions that prevent them from living an active lifestyle. Because of that the importance of informational-educational campaigns is often stressed and their aim is to emphasise the benefits that an active lifestyle provides. The goal of this work is to present the benefits that elderly gain by undertaking an active lifestyle, to outline the barriers and motifs regarding seniors' physical activity and to focus on pro-health initiatives set on popularizing physical activity in groups 65+. The method of literary analysis was applied. Concluded based on literary analysis: 1. Regularly undertaken physical activity is the determining factor of keeping good health condition as well as independence among seniors 2. It is imperative to broaden the spectrum of initiatives regarding seniors' active lifestyle, especially concerning physical activity, by successive introduction of preventing agendas in terms of successful ageing process 3. Regular physical activity adjusted to a senior's condition keeps at bay following issues: potential disabilities, dependence on third party and institutionalised care. It boosts the probability of having an independent and comfortable senility.